Prehistoric Human-Environment Interaction in Eastern North America - Munoz, Samuel E (University of Ottawa (Canada), 2010)
Industrialized human societies both affect and are vulnerable to environmental change, but the dynamics of human-environment relationships during prehistory are less well understood. Using large databases of accumulated paleoecological and archaeological records, this dissertation explores the relationship between prehistoric humans and environmental change in eastern North America. A synthesis of late Quaternary paleoecological and archaeological data from the northeastern United States shows a close temporal correspondence between changes in climate, terrestrial ecosystems, human culture and population numbers. These synchronous changes occurred at 11.6, 8.2, 5.4 and 3.0 thousand years before present, before the adoption of maize agriculture when human groups in eastern North America subsisted by hunting and gathering. Further examination of these datasets in southern Ontario over the last two thousand years found that clearance of forests by prehistoric Native Americans for agricultural fields significantly altered terrestrial ecosystems at a sub-regional scale (102-10 3 m). Together, these results support the hypothesis that prehistoric Native Americans had a greater environmental impact than previously believed, but show that this impact was concentrated around agricultural settlements and was less substantial than that associated with European settlement during the historic period. The methodologies developed in this dissertation provide a means to better understand human-environment relationships in other regions which differ in their environmental and cultural histories.
Keywords: Anthropology, Archaeology.; Geography.; Paleoecology.